Hydraulic characteristics of axial check valves available on the Polish market - Mańko, Robert; Ewertowski, Ryszard (Instal, 2021)
The paper presents the results of measurements of head losses in check valves. The measurements were limited to the typical diameters used in domestic water supply systems. For analysis, valves of 3 producers were proposed, readily available in general installation and construction stores. For each valve, the parameters of local loss coefficient changes as a function of the flow velocity were determined and on their basis, the average values of the coefficients were calculated, which could be the basis to designing the installation with check valves. Moreover, the article presents the results of measurements of cracking pressure („opening”) through the valves.
Keywords: check valve; local loss coefficient; cracking pressure